Clinical features, comorbidity, and cognitive impairment in elderly bipolar patients - Rise IV; Haro JM; Gjervan B (Neuropsychiatric Disease and Treatment, 2016)
Ida Vikan Rise,1 Josep Maria Haro,2–4 Bjørn Gjervan,5,61Department of Psychiatry, Sorlandet Hospital, Arendal, Norway; 2Research Unit, Parc Sanitari Sant Joan de Déu, Sant Boi de Llobregat, Spain; 3Faculty of Medicine, Universitat de Barcelona, Barcelona, Spain; 4CIBERSAM (Centro de Investigación Biomédica En Red de Salud Mental), Madrid, Spain; 5Department of Psychiatry, North-Trondelag Hospital Trust, Levanger, Norway; 6Department of Medicine, Institute of Neuromedicine, Norwegian University of Science and Technology, Trondheim, NorwayIntroduction: Data specific to late-life bipolar disorder (BD) are limited. Current research is sparse and present guidelines are not adapted to this group of patients.Objectives: We present a literature review on clinical characteristics, comorbidities, and cognitive impairment in patients with late-life BD. This review discusses common comorbidities that affect BD elders and how aging might affect cognition and treatment.Methods: Eligible studies were identified in MedLine by the Medical Subject Headings terms “bipolar disorder” and “aged”. We only included original research reports published in English between 2012 and 2015.Results: From 414 articles extracted, 16 studies were included in the review. Cardiovascular and respiratory conditions, type II diabetes, and endocrinological abnormalities were observed as highly prevalent. BD is associated with a high suicide risk. Bipolar elderly had an increased risk of dementia and performed worse on cognitive screening tests compared to age-matched controls across different levels of cognition. Despite high rates of medical comorbidity among bipolar elderly, a systematic under-recognition and undertreatment of cardiovascular disease have been suggested.Conclusion: There was a high burden of physical comorbidities and cognitive impairment in late-life BD. Bipolar elderly might be under-recorded and undertreated in primary medical care, indicating that this group needs an adapted clinical assessment and specific clinical guidelines need to be established.Keywords: bipolar disorder, aged, comorbidity, cognition, impairment, treatment